Stability investigation of the flood protection structure at Nava Nakorn industrial estate, Thailand. (July 2022) - Hoy, Menglim; Udomchai, Artit; Yeanyong, Chakkrid; Horpibulsuk, Suksun; Arulrajah, Arul
Highlights: In 2011, flooding resulted in significant economic losses for this industrial zone. A permanent flood protection wall was built around the industrial area. A large navy watercraft for generating water pressure on flood wall was performed. FEM was performed to examine FS against external and internal failures. Stability of the flood protection wall was confirmed. Abstract: A flood protection structure was built around the industrial area of Nava Nakorn in Pathum Thani Province, Thailand to ensure the safety of the industrial estate. Three types of flood protection walls were constructed and completed in 2012, which were prestress corrugated concrete sheet pile and reinforced concrete retaining wall. A large-scale experiment using a large navy watercraft for generating the water pressure on the flood protection structure was performed. Finite element analysis for simulation the flooding over 4 months was also performed. Factor of safety (FS) against external and internal failures decreased with increasing the flooding levels; however, all FS values were higher than the typical requirement for geotechnical design. All bending moments and shear stress in the flood protection walls were found to be lower than the required design values. The knowledge gained from this research can be applied to other flood walls, in similar soft clay deposits.